The power of regret : how looking backward moves us forward - Pink, Daniel H. (Riverhead Books, 2022)
"From Daniel H. Pink, the #1 New York Times-bestselling author of When and Drive, a new book about the transforming power of that crucial and misunderstood emotion, regret. "Regret is not dangerous or abnormal, it is healthy and universal, an integral part of being human," Daniel H. Pink writes in his provocative and eye-opening new book. "Done right, it needn't bring us down; it can lift us up." Drawing from new research in social psychology, neuroscience, biology, and more, as well as from more than ten thousand people in thirty-five countries around the world who responded to his World Regret Survey--the largest of its kind ever conducted--Pink challenges the idea of regret being a drag on our self-esteem and outlook. In fact, understanding how regret actually works and using those insights to reframe our perspective of it will help us reclaim regret as an indispensable emotion that can help us make smarter decisions, perform better at work and school, and bring greater meaning to our lives. As he did in his other paradigm-changing books When, Drive, and A Whole New Mind, Pink sets down a dynamic new way of thinking about regret and frames his ideas in ways that are clear, accessible, and pragmatic. Packed with true stories of people's regrets as well as practical takeaways for reimagining regret as a positive force in your own life, this book shows how we can live richer, more engaged lives--with no regrets"--